Disseminated tuberculosis presenting as lytic bone lesions: A diagnostic challenge in pediatric oncology (Indian Journal of Case Reports, 2026)
Lytic bone lesions in children often raise concern for malignancy, with differentials including Langerhans cell histiocytosis, Ewing’s sarcoma, lymphoma, and metastatic neuroblastoma. In tuberculosis (TB) endemic regions, however, infectious causes must also be considered to avoid misdiagnosis and unnecessary oncologic interventions. We report a case series of two immunocompetent children who presented to a pediatric oncology unit with multiple lytic skull lesions. Both had a family history of TB. Initial suspicion was for malignant disease, but histopathological examination confirmed TB. One child had disseminated craniofacial and vertebral involvement, while the other showed multifocal osseous disease, including the mandible, sternum, and scapula. Both children were managed successfully with anti-tubercular therapy in accordance with National TB Elimination Program (NTEP) guidelines. Although osseous TB accounts for only 5–6% of extrapulmonary TB, and multifocal skeletal involvement is rare, TB remains an important differential diagnosis for pediatric lytic lesions in endemic regions. Pediatric oncologists should remain vigilant for TB when evaluating children with multifocal lytic lesions, as early recognition can prevent unnecessary invasive procedures and inappropriate oncologic treatments.